2014
DOI: 10.1097/mao.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic Membrane Manipulation to Treat Symptoms of Patulous Eustachian Tube

Abstract: Cartilage tympanoplasty provides a safe and accessible surgical option for the treatment of PET and significantly reduces the symptoms of autophony, conducted breath sounds, and aural fullness. Further studies are needed to investigate whether addressing PET symptoms simultaneously from both the tympanic membrane and the eustachian tube orifice can improve patient symptoms even further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 13 publications
0
18
0
4
Order By: Relevance
“…27 In patients in whom tympanostomy tubes are effective, they may work by mass loading the tympanic membrane or by providing a route for pressure equalization, thereby minimizing excursions of the tympanic membrane. 28 In this series, 33% of patients underwent tympanostomy tube placement prior to pursuing additional treatment, and 20% (n = 5) reported that the tube made their symptoms worse. Some patients undergoing ET surgery also had a tympanostomy tube placed during the procedure in order to address temporary ET dilatory dysfunction caused by the procedure.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…27 In patients in whom tympanostomy tubes are effective, they may work by mass loading the tympanic membrane or by providing a route for pressure equalization, thereby minimizing excursions of the tympanic membrane. 28 In this series, 33% of patients underwent tympanostomy tube placement prior to pursuing additional treatment, and 20% (n = 5) reported that the tube made their symptoms worse. Some patients undergoing ET surgery also had a tympanostomy tube placed during the procedure in order to address temporary ET dilatory dysfunction caused by the procedure.…”
Section: Discussionmentioning
confidence: 79%
“…Although placement of a tympanostomy tube has been reported to reduce symptoms in up to 54% of patients with PETD, it may also exacerbate them . In patients in whom tympanostomy tubes are effective, they may work by mass loading the tympanic membrane or by providing a route for pressure equalization, thereby minimizing excursions of the tympanic membrane . In this series, 33% of patients underwent tympanostomy tube placement prior to pursuing additional treatment, and 20% (n = 5) reported that the tube made their symptoms worse.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Various surgical approaches for severe PET have been reported, 2 such as suture ligation, 6 soft-tissue bulking agent 7 or hydroxyapatite 8 injection, implantation of autologous cartilage, 1 infusion of gelatin sponge solution, 9 transection of the tensor veli palatine muscle, 10 ventilation tube placement, and tympanic membrane manipulation. 11,12 Plugging of the ET was reported using a catheter, 13 angiocut catheter filled with bone wax, 14,15 cartilage, 16 and silicone plug. 3,4,17 The silicone plug (Kobayashi Plug ) has advantages over other materials due to its safety and exchangeability when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals suffering from eustachian tube dysfunction (ETD), the tube opening may be obstructed, resulting in the typical complaints of ear fullness, muffled hearing, ‘popping’ sounds or tinnitus . Less frequently, the ET may be permanently patulous, resulting in the symptoms of aural pressure or autophony …”
Section: Introductionmentioning
confidence: 99%